Pour un manuel de légistique - Le May, Denis (Les Cahiers de droit, 1980)
The purpose of this paper is to advocate the creation of a legislative drafting manual that would suit the needs of all those concerned with the legislative process. The order and editing of the Manual are examined in two successive parts. The proposed Manual outlines an editing, conservation and retrieval method. A comprehensive classification scheme would cover all steps, all aspects and all fields of legislation. An editor / coordinator would assure control and follow-up on the Manual which would be published in parts, through a Bulletin. The classification scheme would allow users to classify all sections or parts according to their needs.